A new genus of cricket with one new species from western Yunnan, China (Orthoptera: Gryllidae: Gryllinae) - Liu, Yun-Fei; Shen, Chu-Ze; Zhang, Ling; He, Zhu-Qing (Zootaxa, 2019)
Most male crickets can produce songs mostly for attracting females. Songs are specific among species,. this depending on physiology and the structural characteristics of the forewings. Nevertheless, some species belonging to subfamily Gryllinae have lost their singing abilities (mute species). Chinese examples include Agryllus spp., Conoblemmus spp., Goniogryllus spp. and Callogryllus yunnanus. Males of these genera are either wingless or have forwings similar to those of females. These crickets have been poorly studied in China. In this study, we describe one new genus Asonicogryllus He gen. nov. with a new species Asonicogryllus kwanghua sp. nov. from western Yunnan. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).